The Relationship Between Home Literacy Environment and Parent Involvement Towards Early Childhood Language Skills in PWP Dama Kumara - Primayana, Kadek Hengki; Dewi, Putu Yulia Angga (Aulad: Journal on Early Childhood, 2022)
The home literacy environment should be used as one of the things that is prioritized in providing home facilities, therefore it will continue to support the process of child development properly, especially language development.The purpose of   this study was to determine the relationship   between the home literacy environment and parent involvement to early childhood language   skills.   In this study, the method used is the correlation method and ex post facto. The data were collected using a questionnaire and to test the hypothesis using the product-moment correlation technique. In this study, it was found that the home literacy environment variable had an effective contribution of 30.89% to early childhood language skills. The parent involvement variable has an effective contribution of 40.65% to early childhood language skills.